Ketegangan antara Kebebasan Berpendapat dan Ketertiban Umum: Studi tentang Aksi Demo dan Kerusakan Fasilitas Umum - Ach Chaidar Ghazy; Isroqunnajah Isroqunnajah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Demonstrations serve as a symbol of public participation in a democratic state, yet they often escalate into anarchic actions that damage public facilities and disrupt social stability. This phenomenon reflects the tension between the ideal of freedom of expression and the reality of mass behavior on the ground. This study aims to examine the causes, dynamics, and legal implications of demonstrations that result in the destruction of public facilities, analyzed through the perspectives of state law and Islamic law. This research employs a qualitative method based on library research by reviewing regulations, academic literature, and the thoughts of both classical and contemporary scholars. The findings reveal that Law Number 9 of 1998 guarantees the right of citizens to express their opinions, while also providing strict limitations on actions that may lead to unrest or damage. Meanwhile, from an Islamic perspective, demonstrations are considered permissible as long as they do not cause harm and adhere to the principles of amar ma’ruf nahi munkar. The destruction of public facilities is classified as fasād, which is prohibited in Islamic law because it violates the principles of preserving property and life (ḥifẓ al-māl and ḥifẓ al-nās). This study concludes that demonstrations can only function as a constructive democratic tool when carried out peacefully, responsibly, and with respect for the public interest. A synergy between the community, security forces, and the state is needed to cultivate a mature and civilized democratic culture that does not harm public spaces.   Keywords: demonstrations, public facilities, Islamic law